The study of AODV routing protocol in Vehicular Ad-hoc Sensor Networks - Suhaili, Sinarwati Mohamad; Marzuki, N.R.A; Jambli, Mohamad Nazim; Lenando, Halikul Bin; Abdullah, Johari Yap (Institute of Electrical and Electronics Engineers Inc., 2015)
In VASNETs, each vehicle carries an intelligent node, which sense the real phenomena and collects the required data. There are many routing protocols that have been proposed and assessed the efficiency of VANETs. However, there are only several research about performance evaluation of routing protocol in VASNETs. In order to fill that gap, in this research we have undergo the performance evaluation of AODV routing protocol in VASNETs. The experiment was setup in order to investigate the effect of different simulation area towards increasing velocity and number of mobile nodes. The tools that been used for this purpose is AVRORA simulation tool. Based on the simulation results obtained, the performance of AODV is analyzed and compared in different sizes of simulation area. The simulation results show the significant different in the variation of simulation area in term of the percentage of packet loss in VASNET